Analisis Faktor-Faktor Sosial Ekonomi yang Mempengaruhi Pendapatan Petani Kakao di Desa Pasapa Kecamatan Budong-Budong Kabupaten Mamuju Tengah Provinsi Sulawesi Barat - Yormawi, Ika (LaGeografia, 2017)
This study aims to find out: 1) What are the socio-economic conditions of cocoa farmers in Pasapa Village 2) What are the factors that influence the income of cocoa farmers in Pasapa Village, Budong-Budong District, Central Mamuju District, West Sulawesi Province. This research is quantitative descriptive research. The population of 500 family heads determines systematically random sampling with a sample of 15% so that 75 respondents can be obtained by respondents. Data collection in this study was carried out by observation, interview, and documentation techniques. The data obtained are then analyzed by descriptive analysis techniques and multiple linear regression analysis using SPSS V.22. The results showed that on average cocoa farmers aged 36-45 years and the length of work as cocoa farmers an average of 15-20 years, the average cocoa farmer household has a total of 4-6 people, education of cocoa farmers in Pasapa Village is still low, where the most frequently found are: elementary school graduates 36.00%. The average income of cocoa farmers is> Rp.5,000,000 - Rp.10,000,000 per year. In order to meet primary and secondary needs, as well as to increase business capital and income, cocoa farmers have other jobs including: rice farmers, oil palm farmers, corn farmers, cattle farmers, entrepreneurs, honor teachers, contract teachers, and civil servants. Based on the research results, cocoa farmers were declared not poor The average use of capital is <Rp.500,000 - Rp.5,000,000. The average area cultivated is 25-75 acres. With the number of production most often found in a month is <50 kg with a percentage of 49.33. The average proceeds from cocoa sales are invested in the education of children of cocoa farmers. Based on the results of the research, the income of cocoa farmers is influenced by the length of work, the number of working hours each to the garden in each day, the age of cocoa, the area of land and the amount of production.